2011
DOI: 10.1007/s00300-011-1000-7
|View full text |Cite
|
Sign up to set email alerts
|

Seabird ticks (Ixodes uriae) distribution along the Antarctic Peninsula

Abstract: The distribution of the tick Ixodes uriae is studied in the South Shetlands and diVerent locations along the Antarctic Peninsula. Ticks were found beneath stones close to penguin rookeries of chinstrap, gentoo and adelie penguin, although no individuals were found parasitized. Our results showed that ticks are not distributed evenly along the Antarctic Peninsula being more common and abundant in the northern part with relative abundances of ticks ranging from 1 to 57 individuals per stone and from 2 to 26% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 25 publications
0
22
1
Order By: Relevance
“…populations by ticks coming from the north, our results suggest rather that north-eastern and south-western populations along the peninsula originate from 2 distinct source populations. These results are particularly surprising given that previous studies have suggested the quasi absence of I. uriae in southern areas of the peninsula (Barbosa et al 2011) and require that we revisit our understanding of this parasite's distribution and the factors that affect it. The tick samples we used in the present study were collected over a 10 yr period.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…populations by ticks coming from the north, our results suggest rather that north-eastern and south-western populations along the peninsula originate from 2 distinct source populations. These results are particularly surprising given that previous studies have suggested the quasi absence of I. uriae in southern areas of the peninsula (Barbosa et al 2011) and require that we revisit our understanding of this parasite's distribution and the factors that affect it. The tick samples we used in the present study were collected over a 10 yr period.…”
Section: Discussioncontrasting
confidence: 43%
“…As 100s of ticks can often be found under a single stone within colonies (e.g. Benoit et al 2007, Barbosa et al 2011see Fig. 1b), these findings suggest that tick population sizes are large and that most populations likely maintain equilibrium genotype frequencies across generations (i.e.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, seven different arthropodborne viruses (arboviruses) were identified in I. uriae ticks collected from King penguin colonies on Macquarie Island in the subantarctic [24]: Nugget virus, Taggert virus, Fish Creek virus, Precarious Point virus, and Catch-me-cave virus, all of which belong to the order Bunyavirales (Nairoviridae and Phleboviridae), a member of the Reoviridae (Sandy Bay virus, genus Orbivurus), and a member of the Flaviviridae (Gadgets Gully virus) [23][24][25]. Notably, I. uriae is the only species of tick with a circumpolar distribution and is found across the Antarctic peninsula [26,27]. I. uriae are mainly associated with nesting seabirds and feed on penguins in the summer months, using off-host aggregation sites for the reminder of the year [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…(Vidal et al unpublished observations)). The absence of blood parasites has been reported in this species (Merino et al 1997;Barbosa and Palacios, 2009), as well as the presence of bacteria, protozoa and ectoparasites, but in low prevalences (Barbosa and Palacios, 2009;Barbosa et al 2011). We used an experimental approach, treating chicks with anthelminthic drugs and comparing them with their siblings injected with PBS as a control.…”
Section: Discussionmentioning
confidence: 99%